Ameloblastic Carcinoma in a 2-Year-Old Child: A Case Report and Review of the Literature. (22nd July 2020) - Vu, Ngoc Bao; Le, Ngoc Tuyen; Chaisuparat, Risa; Thunyakitpisal, Pasutha; Tran, Ngoc Minh
Abstract : Ameloblastic carcinoma (AC) is a rare malignant odontogenic tumor in pediatric patients, only 22 cases have been reported in literature since 1932. We present an extremely rare case in which AC occurred in a 2-year-old girl, who had a tumor in the right mandible. Radiographic findings showed a multilocular, poorly defined, and mixed radiolucent-radiopaque lesion in the region of teeth #84 to #85, with bone and tooth root resorption. Computed tomography revealed buccal cortex destruction, tumor infiltration of soft tissue, and enlarged nodes. Incisional biopsy showed histomorphological features of AC. Immunohistochemical analysis exhibited a positive result for Cytokeratin (CK) 19 and overexpression of p53 and Ki67. The patient underwent right hemimandibulectomy and neck dissection. The final pathology was consistent with the initial diagnosis of AC. The patient did not exhibit signs of recurrence or metastasis within 2 years postoperatively. Given the rarity of this disease and the age of the patient, this report constitutes a valuable contribution to the current literature.